STRATEGI PRODI MANAJEMEN KEUANGAN SYARIAH DALAM MENGEMBANGKAN MINAT MAHASISWA BERWIRAUSAHA - Marhaban, Marhaban (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
The development of entrepreneurship spirit has become a crucial things for the future of students. In supporting the emergence of high competitiveness, function and role of educators to be more active in providing motivation for learners to become entrepreneurs is indispensable. College as one of the means and facilitating role in shaping the young generation has an obligation to train and motivate the students to be come savvy generation, independent, creative, innovative and able to create business opportunities. Thus, every college immediately towards sole discreation to balance between higher education research institutions with entrepreneurs forming institutions. Alumni are required to be innovative and creative in terms of their personal development through the creation of level playing field, so that future expected with extensive job creation, economic growth in the region will increase.The aims of this study is to analyze the strategic of program study of law economic syariah should do to improve the interest of being entrepreneur of student.